Surfactant-derived water-soluble carbon dots for quantitative determination of fluoride via a turn-off–on strategy. (13th December 2021) - Kainth, Shagun; Goel, Neha; Basu, Soumen; Maity, Banibrata
Abstract : Surfactants play a vital role as precursors for achieving carbon cores, heteroatom π-systems, and stability in carbon dots (CDs). Abstract : Surfactants play a vital role as precursors for achieving carbon cores, heteroatom π-systems, and stability in carbon dots (CDs). Herein, we report novel water-soluble fluorescent carbon-dots (WCDs) prepared by a microwave pyrolysis technique using cetylpyridinium chloride (CPC) as a precursor. The as-prepared WCDs showed yellow emission ( λ em = 545 nm) with excitation wavelength–dependent emission property, significant quantum yield (34.6%) and an average lifetime value in the range of 1.11 ns. The synthesized WCDs were characterized by transmission electron microscopy, X-ray photoelectron spectroscopy, zeta potential measurement, steady-state fluorescence spectroscopy and time-resolved fluorescence emission lifetime analysis. The result revealed that the WCDs are monodisperse in nature with a uniform particle size of 2.5 nm, a higher degree of surface oxidation state (oxygen content is 11.63%) and a positive value of surface charge density (+63 mV). In addition, we have evaluated the effect of different iron oxidation states (Fe n +, n = 2 and 3) on the photoluminescence (PL) properties of the WCDs, which showed different extents of PL quenching (Fe 2+ = 36% and Fe 3+ = 59%). Furthermore, the WCDs@Fe n + ( n = 2 and 3) system was examined for the detection and quantification of fluoride (F − ) anions. Mainly, the WCDs@Fe 3+ system showed effective fluorescence recovery in the presence of F − ions with LOD = 1.26 μM, while the WCDs@Fe 2+ nanoprobe was inactive towards F − ions. To validate the turn-off–on strategy, time-resolved emission decays were recorded for the WCDs and the WCDs@Fe n + system in the presence of F − anions. The studies showed profound recovery in a lifetime for the WCDs@Fe 3+ system in the presence of F − anions that supports the development of the strategy. All our findings show that by using a single precursor-like surfactant, it is possible to make long–range emissive CDs, which could be useful in the qualitative and quantitative determination of multiple analytes via a turn-off–on strategy.